Responsible patterns of production and consumption: The race for the achievement of SDGs in emerging markets (2021)
Since the end of the 20th century, the role of private multinational enterprises (MNEs) has been recognized as critical in implementing increased sustainable production and consumption atterns. Particularly after the creation of the Sustainable Development Goals (SDGs) and the Agenda 2030, this role has increased. In this sense, this paper aims to analyze the measures and actions taken by companies in their contribution to the achievement of the SDG 12. Through the identification of more than 52 metrics in sustainability reports of 854 firms, findings suggest that direct greenhouse gas emissions and indirect greenhouse gas emissions are the most often reported corporate metrics to measure their impact on specific SDGs. This reveals the importance of sustainability actions in emerging market firms as a mechanism to gain legitimacy when operating in foreign markets and as an opportunity to create more sustainable production models.